Peningkatan Kualitas Masyarakat Melalui Sosialisasi Sadar Wisata dan Sapta Pesona - Soeswoyo, Dina Mayasari (Jurnal Pemberdayaan Pariwisata; Vol 2 No 1 (2020): Jurnal Pemberdayaan Pariwisata, 2020)
Community service programs on the promotion of Tourism Awareness and Enchantment to the Batulayang Tourism Village community need to be carried out based on initial observations and requests from the Village Tourism Awareness Group (Pokdarwis). This Tourism Village   has begun to be visited by many tourists because it has a variety of natural and cultural attractions, but at that time the Pokdarwis found it difficult to socialize to the local community a variety of knowledge gained from the Bogor Regency Tourism Office. The activity was divided into two sessions, namely an educational session through lectures and question and answer discussions, as well as training sessions and competitions between community groups consisting of the tour village manager, Pokdarwis, home-stay owners and food and beverage shop entrepreneurs. The participants seemed enthusiastic during the education and training. At the beginning and end of the program, pre-test and post-test are conducted to measure the increase in community understanding. The results of the mean pre-test and post-test showed the level of understanding of the participants progressed from the moderate category but tended to be poor to very good. Socialization of Tourism Awareness and Enchantment is very important for the community as a basis for understanding of tourism so that it can foster motivation and responsible participation in the development of tourism villages .